1990
DOI: 10.1007/bf01647248
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Endothelin bei Normalpersonen und Patienten mit nephrologisch-rheumatologischen und kardiovaskulären Erkrankungen

Abstract: Plasma concentrations of the recently isolated potent vasoconstrictory peptide endothelin were measured in 382 patients. The investigations were performed by means of a sensitive radioimmunoassay specific for Endothelin-1, 2. The results from 110 healthy volunteers displayed a normal range of 44.67 +/- 3.51 pg/ml. Significantly raised levels were found in 33 patients with chronic end-stage renal failure both before and after hemodialysis. In contrast, 35 patients with compensated renal insufficiency did not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Conflicting results have been reported on endothelin plasma levels in pregnant women with hypertension. Some authors observed decreased plasma endothelin levels in women with hypertension and proteinuria (Schrader et al . 1990), and recent reports showed significantly higher plasma endothelin levels in women with pregnancy‐induced hypertension compared with normotensive pregnant women (Kamoi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported on endothelin plasma levels in pregnant women with hypertension. Some authors observed decreased plasma endothelin levels in women with hypertension and proteinuria (Schrader et al . 1990), and recent reports showed significantly higher plasma endothelin levels in women with pregnancy‐induced hypertension compared with normotensive pregnant women (Kamoi et al .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, plasma ET levels are significantly elevated in the patients with cirrhosis. 9 These studies raise the possibility that ET-1 may be involved in the pathogenesis of portal hypertension in various liver diseases.…”
mentioning
confidence: 99%
“…In view of the potent pressor effects of ET-1, systemic hypertension was early recognized as target for ET antagonism [Schrader et al, 1990]. Moreover, circulating ET-1 concentration is elevated in patients with essential hypertension [Saito et al, 1990].…”
Section: Studies In Hypertensionmentioning
confidence: 99%